Penerapan Terapi Menggambar untuk Menurunkan Gejala Halusinasi Pada Pasien Skizofrenia di RSJD Dr. Arif Zainudin Surakarta - Aziizun Chaulian; Sitti Rahma Soleman; Tri Andri Pujiyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Schizophrenia is a mental disorder with positive symptoms of hallucinations, patients hear voices and see things that do not exist. Patients with confusion and negative symptoms feel indifferent and often lose their emotions. Therefore, non-pharmacological therapy, such drawing therapy, a form of communication. Therefore the artistic media. Patients with hallucinations can express their feelings and thoughts through drawings, distracting them from unrealistic hallucinations. Objective: The general is to determine and evaluate hallucination symptoms after drawing therapy administered to schizophrenia patients at Dr. Arif Zainudin Mental Hospital, Surakarta. Method: A case study design was conducted on two schizophrenia patients with hallucinations, in the Bisma and Kresna Rooms of Dr. Arif Zainudin Mental Hospital, Surakarta, from February 28, 2026, to March 6, 2026. The intervention was drawing therapy. Data were collected using AHRS (pre-post test) questionnaire. Implementation Results: Both respondents experienced a decrease in hallucination levels. Respondent 1's hallucination score decreased from 32 (severe hallucinations) to 18 (moderate hallucinations). Respondent 2's hallucination score decreased from 33 (severe hallucinations) to 21 (moderate hallucinations).Conclusion: This study shows that drawing therapy reduces hallucination symptoms. Drawing activities improve patients' concentration and focus, allowing respondents to control their hallucinations.